Membentuk Karakter Masyarakat Sesuai Kepribadian Ash-Habul Jannah Dalam Al-Qur’an - Fadhilatul Hikmah, Wahyu; Simbolon, Parlindungan; Purnamasari, Ayu; Amin, Muhammad; Nikmah, Nikmah; Saputra, Waldi; Tryana , Nofita (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2024)
Humans were created from various tribes and nations to get to know each other. According to the Qur'an, humans are naturally social creatures and live in society. Several verses in the Qur'an instruct humanity to always think about forming a society with certain qualities, so that it is very possible for humanity to reconstruct a picture of an ideal society based on the instructions of the Qur'an. In the Islamic view, society is a means for implementing Islamic teachings concerning living together and side by side, so society must become the basis for the framework of worldly life for the unity and cooperation of the people towards a human growth that realizes equality and justice. This community service aims to grow the Muslim community's awareness of the poor and those in need. This service was carried out in South Tengkerang District, Pekanbaru, Riau. The extension program is implemented using the PAR (Participatory Action Research) method, which involves researchers and participants in collaboration to encourage active participation, feedback and joint knowledge creation. One proof of the transformational power of this training is the fact that the community admits that the training has changed their understanding of social life by emulating the personality of ash-Habul Jannah based on the Koran. Living side by side in society cannot be separated from the attitude of sharing with the poor and people in need